The Influence of Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) Through Net Present Value (NPV) in State-Owned Banks for the Period 2015 - 2024 - Windi Triani; Heidi Siddiqa; Ardhiansyah Ardhiansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research intends to investigate how the Loan to Deposit Ratio (LDR) and the Debt to Equity Ratio (DER) influence Return on Equity (ROE) via Net Present Value (NPV) in state-owned banks over the period from 2015 to 2024. A quantitative method was employed for this analysis, making use of secondary data processed through the SEM-PLS technique for Structural Equation Modeling, with SmartPLS software version 4.0 aiding in the computations. The analysis process involves examining the outer model, checking the model fit, and assessing the inner model. The results indicate that LDR negatively and insignificantly affects ROE, whereas DER positively and significantly influences ROE. Additionally, LDR presents an insignificant negative effect on NPV, in contrast to DER, which has a notably beneficial effect on impact on NPV. It was observed that NPV has a beneficial yet trivial impact on ROE. During the indirect effect assessment, LDR did not demonstrate a meaningful effect on ROE through NPV. In contrast, DER revealed a positive yet insignificant effect on ROE through NPV.